Structural mechanism of synergistic activation of Aurora kinase B/C by phosphorylated INCENP - Kamal R. Abdul Azeez (Nature Portfolio, 2019)
The inner centromere protein (INCENP) activates Aurora kinase B (AURKB) and Aurora kinase C. Here the authors provide insights into the activation mechanism of AURKB/C by determining the crystal structure of fully active phosphorylated human AURKC bound to the phosphorylated C-terminal IN-box section of human INCENP.